Magnitude of Prompt HIV-Seropositive Status Disclosure to Partner and Associated Factors among Adult Clients on ART at Holeta Health Center, Central Ethiopia, 2020. (13th May 2022) - Kebede, Guta; Dufera, Adugna; Kolola, Tufa; Girma, Teka; Belema, Daniel
Abstract : Background . Disclosure of HIV-seropositive status is important for HIV prevention and maintenance of health for people living with HIV and the community at large. Most of the disclosure in our country and elsewhere were after putting the partner at risk of contracting HIV/AIDS. This study aimed to assess prompt HIV-seropositive status disclosure to partner and its associated factors among people living with HIV and attending care and treatment at a health center, in central Ethiopia. Methods . A cross-sectional study was carried out from September 15, 2019, to March 15, 2020, among 438 people living with HIV who were more than 18 years old and had sexual partner attending ART clinic at Holeta Health Center, central Ethiopia. The data were collected through face-to-face interviews using a structured questionnaire. The data were entered into Epi data version 3.1 and exported to SPSS version 21 for analysis. Descriptive analysis was conducted to determine the magnitude of prompt HIV seropositive status disclosure to partner and multivariable logistic regression analysis was computed to identify factors associated with prompt HIV seropositive status disclosure. Results . A total of 434 study participants took part in this study giving a response rate of 99%. Three hundred thirteen (72.1%) respondents disclosed their seropositive status to their partners promptly. Being married (AOR = 2.99, 95% CI = 1.09–8.21), less than 24-months duration on treatment (AOR = 0.185, 95% CI = 0.076–0.454), discouraging response of partner about the test (AOR = 0.34, 95% CI = 0.0149–0.780), knowing serostatus of one's own partner (AOR = 10.42, 95% CI = 4.19–25.19), and using condom always with a partner (AOR = 11.44, 95% CI = 3.37–38.79) were factors significantly associated with prompt HIV seropositive status disclosure to partner. Conclusion . The proportion of prompt disclosure of HIV seropositive status to partner was low when compared to the overall partner disclosure rate. Being in marriage, less than 24 months duration on treatment, discouraging response of partner about the test, knowing serostatus of one's partner, and using condom always with a partner were identified as predictors of prompt HIV seropositive status disclosure to partner.